2016
DOI: 10.1007/s10096-016-2711-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical prediction rules in Staphylococcus aureus bacteremia demonstrate the usefulness of reporting likelihood ratios in infectious diseases

Abstract: Infectious diseases specialists often use diagnostic tests to assess the probability of a disease based on knowledge of the diagnostic properties. It has become standard for published studies on diagnostic tests to report sensitivity, specificity and predictive values. Likelihood ratios are often omitted. We compared published clinical prediction rules in Staphylococcus aureus bacteremia to illustrate the importance of likelihood ratios. We performed a narrative review comparing published clinical prediction r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…We compared the concordance between the predictions and the final microbial etiologies for the experts and for the algorithm and calculated sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and likelihood ratios (LRs) for the predictions [12]. Given the importance of this diagnostic prediction in the patient's therapeutic management, we determined that the discriminant properties should be "high" (LR + > 10 and/ or LR-< 0.1) for the prediction to be considered useful for clinical practice [13,14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared the concordance between the predictions and the final microbial etiologies for the experts and for the algorithm and calculated sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and likelihood ratios (LRs) for the predictions [12]. Given the importance of this diagnostic prediction in the patient's therapeutic management, we determined that the discriminant properties should be "high" (LR + > 10 and/ or LR-< 0.1) for the prediction to be considered useful for clinical practice [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…", as the discriminant ability between the two diagnoses was considered low. We interpreted our results mainly based on the calculation of likelihood ratios, as recommended for reports of a diagnostic test for an infectious disease [12]. Likelihood ratios incorporate both sensitivity and specificity and, unlike predictive values, do not vary with prevalence, making them good statistical tools to facilitate translation of knowledge from research to clinical practice [12].…”
Section: Discussionmentioning
confidence: 99%
“…We compared the concordance between the predictions and the final microbial etiologies for the experts and for the algorithm and calculated sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and likelihood ratios (LRs) for the predictions [11]. Given the importance of this diagnostic prediction in the patient's therapeutic management, we determined that the discriminant properties should be "high" (LR +> 10 and/or LR-< 0.1) for the prediction to be considered useful for clinical practice [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…", as the discriminant ability between the two diagnoses was considered low. We interpreted our results mainly based on the calculation of likelihood ratios, as recommended for reports of a diagnostic test for an infectious disease [11]. Likelihood ratios incorporate both sensitivity and specificity and, unlike predictive values, do not vary with prevalence, making them good statistical tools to facilitate translation of knowledge from research to clinical practice [11].…”
Section: Discussionmentioning
confidence: 99%
“…Still, there are only a few studies in which the optimal ndings have been reported to differentiate between them by Gram stain. 11 Therefore, the current study aims to investigate the contributable ndings in Gram stain to identify CoNS and distinguish it from SA.…”
Section: Introductionmentioning
confidence: 99%